2022
DOI: 10.1111/cns.13966
|View full text |Cite
|
Sign up to set email alerts
|

Insights about circadian clock in glioma: From molecular pathways to therapeutic drugs

Abstract: Glioma is characterized as the most aggressive brain tumor that occurred in the central nervous system. The circadian rhythm is an essential cyclic change system generated by the endogenous circadian clock. Current studies found that the circadian clock affects glioma pathophysiology. It is still controversial whether the circadian rhythm disruption is a cause or an effect of tumorigenesis. This review discussed the association between cell cycle and circadian clock and provided a prominent molecular theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…58 Besides, accumulating evidence reveals that the circadian rhythm has an impact on glioma pathophysiology, and the internal characteristics concerning the circadian clock in glioma involve stemness, metabolism, radiotherapy sensitivity, and chemotherapy sensitivity. 59 Meanwhile, alterations of microbiome-derived metabolites such as ergothioneine were observed to be associated with circadian function. 60 Yet, it remains to be addressed whether the gut microbiota may affect tumorigenesis through disruption of circadian rhythm.…”
Section: Microbiota-derived Metabolites and Productsmentioning
confidence: 99%
“…58 Besides, accumulating evidence reveals that the circadian rhythm has an impact on glioma pathophysiology, and the internal characteristics concerning the circadian clock in glioma involve stemness, metabolism, radiotherapy sensitivity, and chemotherapy sensitivity. 59 Meanwhile, alterations of microbiome-derived metabolites such as ergothioneine were observed to be associated with circadian function. 60 Yet, it remains to be addressed whether the gut microbiota may affect tumorigenesis through disruption of circadian rhythm.…”
Section: Microbiota-derived Metabolites and Productsmentioning
confidence: 99%
“…The discovery of molecular mechanisms regarding radio/chemo resistance and biomarker detection could improve the strategy for novel therapeutics [15][16][17].…”
Section: New Insight On Molecular Involvements Of Gliomasmentioning
confidence: 99%
“…Accumulating evidence reveals that the circadian rhythm has an impact on glioma treatment; particularly, a recent study highlighted that GBM cells exhibited a significant temporal response to bortezomib, used as a proteosome inhibitor in recurrences stages of GBM treatment [67,68]. Moreover, Wagner et al [17] demonstrated the higher efficacy of low-dose Bortezomib treatment when administered in tumor-bearing animals at night compared to day/night administration, although the effect of chronotherapy treatment in glioma is still controversial and needs further large-population-based trials for validation.…”
Section: Clock/bmal1 Gene As Therapeutic Targetmentioning
confidence: 99%
“…About one-third of intracranial tumors are gliomas, the most frequent malignant tumor inside the brain that arises from the central nervous system (CNS) [ 1 , 2 ]. According to molecular staging, tumor cell anisotropy, mesenchymal degeneration, nuclear fission activity, degree of microvascular proliferation, and degree of tumor necrosis, the World Health Organization divides gliomas into low-grade and high-grade gliomas [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%